DAMPAK PERKAWINAN DIBAWAH UMUR PERSPEKTIF MADZHAB IMAM SYAFI’I (Studi Pada Masyarakat Bajo Di kawasan Wisata Bokori ) - Hasniran Hasniran (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
Underage marriage in the Bajo community in the Bokori Tourism area, shows that it is still being implemented and the impact it has is the impact on husband and wife, the impact on children, the impact on each family, the impact on divorce, the impact on the quality of education, the impact on the economy, the impact on health, the impact on psychology. According to the Syafi'i school of thought, a marriage can be carried out if the prospective bride and groom are of baligh age and parents should ask their child for approval so that there is no feeling of being forced when the marriage takes place. So that this is the basis for parents who will marry their children even though they are still underage and this continues for generations from their grandmothers to mothers and so on to their children. But not only parents, but teenagers who want to carry out underage marriages also need to think about and prepare all possibilities so that problems do not occur which cause a breakdown in a household